1991
DOI: 10.1104/pp.96.4.1053
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in Plants Infected by Citrus Exocortis Viroid or Treated with Silver Ions and Ethephon

Abstract: The levels of polyamines in leaves of Gynura aurantiaca DC and tomato, Lycoperskon esculentum Mill. cv Rutgers, infected with citrus exocortis viroid (CEVd) or treated with silver nitrate or ethephon (2-chloroethylphosphonic acid) were measured by HPLC in relation to development of symptoms. Previously it had been demonstrated that treatment of G. aurantiaca plants with silver nitrate or ethephon closely mimicked the effects of viroid infection in the plants. In the studies reported here, a marked decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…Probably, fungal PAs would not be transported out of the infected organ (Rifai et al 2005), so all the fluctuations observed in grapevine leaves would be a plant response to the root pathogen. Several authors (Belles et al 1991;Edreva 1997;Rifai et al 2004) also observed a lower concentration of free PAs as a consequence of pathogenic infections. It has been suggested that PAs decrease in these interactions is a non-specific response to tissue damage or to a senescent status of leaves (Edreva 1997;Rifai et al 2004), as low PA levels are often characteristic of tissues where metabolism has slowed down (Galston and Kaur-Sawhney 1990).…”
Section: Discussionmentioning
confidence: 92%
“…Probably, fungal PAs would not be transported out of the infected organ (Rifai et al 2005), so all the fluctuations observed in grapevine leaves would be a plant response to the root pathogen. Several authors (Belles et al 1991;Edreva 1997;Rifai et al 2004) also observed a lower concentration of free PAs as a consequence of pathogenic infections. It has been suggested that PAs decrease in these interactions is a non-specific response to tissue damage or to a senescent status of leaves (Edreva 1997;Rifai et al 2004), as low PA levels are often characteristic of tissues where metabolism has slowed down (Galston and Kaur-Sawhney 1990).…”
Section: Discussionmentioning
confidence: 92%
“…Studies conducted so far in relation with the role of PAs in plant-pathogen interactions have focused mainly on viruses (Negrel et al, 1984;Bellés et al, 1991;Torrigiani et al, 1997;Yamakawa et al, 1998;Hiraga et al, 2000;Marini et al, 2001;Yoda et al, 2003;Yoo et al, 2004) and biotrophic fungi causing rusts and mildews on several different hosts (Walters et al, 1985;Walters and Wylie, 1986;Cowley and Walters, 2002). However, the attention previously devoted to the effects of necrotrophic plant pathogens on host PA metabolism has been very scant (Angelini et al, 1993;Rea et al, 2002).…”
Section: Changes In Pa Metabolism Of Tobacco Plants Infected By the Nmentioning
confidence: 99%
“…Proteolytic activity was assessed spectrofluorometrically with FITC-casein (Sigma) as a substrate (Vera and Conejero, 1988;Belles et al, 1991). The reaction mixture (2.6 mL), containing 150 mm potassium citrate buffer, pH 6.1, 1.5 mm DTT, 513 g of FITC-casein, and 800 L of enzyme extract (2.1-2.9 mg of protein), was incubated at 37°C in the dark.…”
Section: Proteinase Extraction and Activitymentioning
confidence: 99%
“…Proteolytic enzymes were extracted from tuber tissue (a composite of three tubers cut from the apical ends, periderm included) with 50 mm potassium citrate buffer, (pH 6.6, 1 g fresh weight mL Ϫ1 ) containing 20 mm KCl, 2 mm MgCl 2 , 5% (w/v) Suc, 1 mm DTT, 0.5% PVP, and 2 mm Na 2 S 2 O 5 (Belles et al, 1991) with a homogenizer. The homogenate was filtered through Miracloth, centrifuged at 30,000g for 30 min, and the supernatant was stored at Ϫ80°C for subsequent proteinase activity assays.…”
Section: Proteinase Extraction and Activitymentioning
confidence: 99%